Analysis of measurement and calculation of MSD complaint of chassis assembly workers using OWAS, RULA and REBA method - Nelfiyanti, .; N. M. Zuki, N. M.; M. F. F., Ab Rashid (Penerbit Universiti Malaysia Pahang, 2022)
Car assembly is a combination of all components that form one completed vehicle unit. The work process is manually done and repeatedly, which contributes to a risk of musculoskeletal disorders (MSD). Chassis assembly is a job with a high level of complexity and associated with MSD risk for its employees. This study consists of 30 assembly activities divided into six groups based on posture and working methods used during the work process. Group A consists of 7 assemblies, Group B consists of 8 assemblies, Group C consists of 5 assemblies, Group D consists of 2 assemblies, Group E consists of 5 assemblies, and Group F consists of 3 assemblies. This study aims to compare the measurement and calculation of the risk level of MSD workers by using the RULA, REBA, and OWAS methods. The results of the measurements and computations acquired using these three approaches yielded the same risk category: 83.33 % medium risk/dangerous in working groups A, C, D, E, and F, and 16.67 % very high risk/highly hazardous in working group B. These six groups, particularly group B, requires immediate attention to reduce worker complaints of MSD.